2021
DOI: 10.3390/plants10030426
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping Unravels the Genetic Control of Seed Vigor under Low-Temperature Conditions in Rapeseed (Brassica napus L.)

Abstract: Low temperature inhibits rapid germination and successful seedling establishment of rapeseed (Brassica napus L.), leading to significant productivity losses. Little is known about the genetic diversity for seed vigor under low-temperature conditions in rapeseed, which motivated our investigation of 13 seed germination- and emergence-related traits under normal and low-temperature conditions for 442 diverse rapeseed accessions. The stress tolerance index was calculated for each trait based on performance under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
2
18
1
Order By: Relevance
“…Whereas the rapeseed germination is easily affected by low-temperature with the delay of seeding times 4 . Low-temperature sensitively at the germination stage is a major challenge for rapeseed cultivation under the late direct-seeding conditions in China 4,7 . It is a breeding goal to select varieties with well germination under both optimal and stressed conditions to adapt the changing temperature under late direct seeding cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas the rapeseed germination is easily affected by low-temperature with the delay of seeding times 4 . Low-temperature sensitively at the germination stage is a major challenge for rapeseed cultivation under the late direct-seeding conditions in China 4,7 . It is a breeding goal to select varieties with well germination under both optimal and stressed conditions to adapt the changing temperature under late direct seeding cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the position of the QTL (qLTGA9-1) on chromosome A09 was mapped around 30.2-Mb apart from each other based on the physical position of linkage markers on ZS11 genome sequence 25 . GWAS mapping from Luo et al (2021) 7 showed the candidate genes to be around the 3.0-Mb position on chromosome A09 based on ZS11 genome sequence 25 related to seed vigor under low-temperature. As the physical distance between the locus and the QTL we identi ed was more than 27 Mb probably rules out, we believe that the QTLs including qLTGC1-1 we found were novel in rapeseed for LTG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The late direct seeding area under rapeseed has continuously increased in recent years, with intensive cropping development. Meanwhile, rapeseed is sensitive to temperatures below 10 °C at germination 4 , 5 . The temperature at late sowing time in China is generally below 10 °C, which leads to a low germination rate and seedling in rapeseed 6 , which ultimately affects yield 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%